PULSE traffic / Nur Nadhirah Damakkhurairi ...[et al.] - Damakkhurairi, Nur Nadhirah; Mussori, Nur Thaqifah; Ab Jabar, Rabi'atul Adawiyah; Ridzuan, Syazwani Afiqah; Abdullah, Qurratu'aini (2019)
Another steps to involve in this project is by developing the project prototype. PULSE Traffic as mentioned, is the innovation and enhancement made to the existing product by adding some Artificial Intelligence technique and motion sensor. Design of the product basically are not based on the amendment made to the current design, but it is measured based on the functionality which is by adding features that involves with the circuit itself and how the camera perform detection (back end development) and how both of this system integrate their data online through cloud (IoT). A survey was conducted to measure the problems currently faced by current solution and through the survey made, we managed to analyze some useful information to measure the effectiveness of our products to the road users. The technology and product description, marketing strategy and financial estimations are discussed and from the projection, FUSE Enterprise is having deficits of RM30,804.00. However, the following years promise a much stable income statement with increasing revenue and active marketing activity are to be expected to increase the sales of PULSE Traffic.